Análise das propriedades eletrônicas e ópticas do YVO4:Eu3+ e do YVO4:Eu2+ a partir de cálculos de primeiros princípios - Carvalho, Felipe Oliveira de (2024)
The study presented in this thesis explored the structural, electronic, and optical properties of the YVO4:Eu3+ compound, a well-known red phosphor, as well as the modifications of these properties under changes in the oxidation state of Eu3+. According to the experiment, the latter occurs when YVO4:Eu3+ is exposed to gamma radiation, which removes electrons from some atoms in the material, making them available for capture by Eu3+ ions. This situation was simulated by adding an electron in the vicinity of Eu3+ and compensating its charge with the positive charge uniformly spread throughout the material’s interior. The study was conducted using state-of-the-art computational methods based on density functional theory. As a starting point, the properties of pure YVO4 were calculated and compared with previous calculations. Simulating exchange and correlation (XC) effects using the "Modified Becke Johnson" (mBJ) potential resulted in a bandgap value of 3.7 eV, very close to the experimental value of 3.8 eV. The YVO4:Eu3+ compound was computationally simulated by constructing the pure YVO4 supercell (48 atoms), where a Y3+ ion was replaced by an Eu3+ ion, generating a crystal matrix containing 2% of impurities. XC effects were simulated using the mBJ potential. For the Eu ion, spin-orbit (SO) interaction was taken into account, while the highly correlated electrons in the 4f subshell were treated with a Hubbard U correction (mBJ+SO+U approach). Different U values were tested to calculate the electronic structure in order to reproduce the experimentally recorded optical absorption (OA) spectrum of YVO4:Eu3+. The value U = 2.5 eV met this criterion, reproducing all the main features of the experimental OA as well as the rich peak structure related to Eu3+ absorption. All of these features were interpreted in terms of the calculated electronic structure. The OA spectrum is found to be highly anisotropic, with predominant absorption of light polarized parallel to the tetragonal c-axis. The introduction of an additional electron into the YVO4:Eu3+ supercell revealed that Eu3+ captures a significant part of its charge (0.3e), without, however, confirming a complete reduction of its oxidation state to 2+, as suggested by the experiment. Nevertheless, the Eu electronic configuration undergoes noticeable changes, with occupied 4f states increasing in energy and approaching the conduction band. This modification significantly alters the optical absorption of Eu, generated by 4f-5d transitions, in contrast to 4f-4f transitions in the case of charge-free YVO4:Eu3+. This fact explains the drastic change in the emission spectrum of gamma-irradiated YVO4:Eu3+, as observed experimentally. Finally, the partial change in the oxidation state of Eu was confirmed by calculating the Eu L-edge absorption, with results showing a shift of the irradiated YVO4:Eu3+ absorption edge to lower energies compared to YVO4:Eu3+.